ПРИМЕНЕНИЕ ОБОБЩЕННОЙ МОДЕЛИ ДИНАМИЧЕСКОЙ ДУГИ ДЛЯ ИССЛЕДОВАНИЯ ИСТОЧНИКОВ ПИТАНИЯ С ЕМКОСТНЫМ ОГРАНИЧЕНИЕМ СВАРОЧНОГО ТОКА - Сидорец , В.Н.; Кункин , Д.Д. (Інститут електродинаміки НАН України, Київ, 2012)
Application of the generalized model of the dynamic arc for the research of burning conditions of the arc, which is powered from a power source with a capacitive limit the welding current, has been proposed. The techniques of transient and stationary processes analysis in the circuit with an AC welding arc and capacitive limitation have been developed. The techniques of studying the stability of the arc in such electric circuits have been discussed. References 3, figures 2.